EFFECT OF POST-TRAUMATIC STRESS DISORDER ON THE HEMOMICROCIRCULATORY BED OF RATS' LARGE BRONCHI AND ITS CORRECTION WITH QUERCETIN - Bilash, S.M.; Koptev, M.M.; Pronina, O.M.; Pirog-Zakaznikova, A.V.; Oliinichenko, Ya.O.; Donchenko, S.V.; Kononov, B.S. (World of Medicine and Biology, 2024)
Today, due to the complex political and socio-economic situation, which is burdened by hostilities, the living conditions and health of Ukrainian citizens have become much more complicated, and the number of stressful and traumatic situations has increased, which can lead to the development of post-traumatic stress disorder. It has been experimentally proven that the lungs are an organ that is extremely sensitive to stressful influences, which can lead to haemomicrocirculation disorders and endothelial dysfunction. The paper presents the results of an experimental study of the post-traumatic stress disorder effect on the hemomicrocirculatory bed of the rats' large bronchi and its correction with quercetin. It has been shown that this factor causes significant morphological changes in the vessels of the hemomicrocirculatory bed of the rats' large bronchi, which are manifested by impaired hemomicrocirculation with the development of blood stasis, arteriolar spasm, dilation of metabolic and capacitive hemomicrovessels with the phenomena of red blood cell diapedesis into hyperhydrated and leukocyte-infiltrated perivascular connective tissue. Intraperitoneal administration of water-soluble quercetin complex once a day for seven days significantly reduced the development of structural changes in the vessels of the hemomicrocirculatory bed of rats' large bronchi, which indicates the effectiveness of this agent as a stress protector.
Keywords: post-traumatic stress disorder; bronchi; hemomicrocirculatory bed; lungs; morphological changes; structural and metabolic changes; correction